Vietnamese early career academics' identity work: balancing tensions between East and West. Issue 6 (3rd June 2022) - Jones, David R.; Gardner, Trang; Bui, Hong
ABSTRACT: Through a narrative analysis of 33 interviews with Vietnamese early career academics, we explore whether a Confucianist/collectivist academic context in Vietnam has a key influence on academics' identity work, within the embrace of encroaching managerialist practices. We show how these academics from 11 universities negotiated identity alignment and identity tensions between such cultural orientation and managerialism. On the one hand, a Confucianist ethic underpinning higher education in Vietnam is likely to encourage academics to engage in managerialist practices, as it promotes harmony and loyalty to their respective university and its global, 'excellence' goals. On the other hand, a cultural underpinning of collegiality can create tension with the individualist nature of managerialist practices. Our recommendations for universities in a similar context are to adapt the more individualistic performative approaches borrowed from the West by crafting their own collegiate, soft managerialist hybrid practices.